Serum free light chains, interferon-alpha, and interleukins in systemic lupus erythematosus. (August 2014) - Jolly, M; Francis, S; Aggarwal, R; Mikolaitis, RA; Niewold, TB; Chubinskaya, S; Block, JA; Scanzello, C; Sequeira, W
Objective: Interleukin-6 (IL-6), interleukin-10 (IL-10), interferon-alpha (IFN-α), and free light chains (FLCs: lambda, kappa) have all been noted to be of importance in systemic lupus erythematosus (SLE). Herein, we quantified and explored the relationship between these inflammatory mediators and disease activity in SLE; and stratified by their current anti-dsDNA antibody status. Methods: Seventy-seven SLE patients underwent assessment of disease activity using the SLE disease activity index (SLEDAI). Serum FLC (lambda, kappa, and total), IL-6, IL-10, and IFN-α were quantified. Demographics of disease characteristics were determined by chart reviews. Statistical analyses included Mann–Whitney test, chi square, and linear regression analyses. Results: Mean (SD) age of the patients was 44.9 ± 12.7 years; SLEDAI (mean ± SD) was 3.4 ± 4.0. Serum lambda FLC levels had a moderate correlation ( r = 0.46 with physician global assessment, 0.44 with SLEDAI) and the strongest correlation with disease activity as compared with other inflammatory mediators including current dsDNA antibody status. After adjusting for prednisone use, the correlation of lambda FLC with PGA ( r = 0.48) and SLEDAI ( r = 0.52) was better than of current dsDNA antibody status with PGA ( r = 0.33) and adjusted SLEDAI ( r = 0.24), respectively. IL-10 and IFN-α activity did not correlate with disease activity. Serum FLC and IL-6 levels could differentiate between active and inactive SLE patients. Serum lambda FLC and IL-6 levels differed significantly among patients with and without current dsDNA antibodies. Serum lambda FLC levels accounted for 31% of variance in SLEDAI scores. Conclusion: Serum FLC and IL-6 are potentially useful biomarkers of disease activity in SLE. Further studies, with larger study sample and longitudinal design, are indicated.